BIO-SOCIAL FACTORS ASSOCIATED WITH HYPERTENSION IN HILLY POPULATION OF TEHRI GARHWAL - Saxena, Praveer Kumar; Saxena, Vartika; Saxena, Yogesh (Indian Journal of Community Health, 2011)
Background: Hypertension is emerging as a major public health problem in India. The diversity and heterogeneity of distribution of the population makes it difficult to arrive at the precise prevalence. Cardiovascular and other chronic diseases are becoming the major causes of morbidity and mortality in India. Now it is found that prevalence of Hypertension also increasing in rural population1. Various risk factors namely age, smoking, salt intake, consumption of alcohol, B.M.I., Diabetes Mellitus are known to be risk factors for many such diseases. The present study was carried out to estimate the prevalence of Hypertension and to identify their biosocial correlates. Objectives: 1.To determines the prevalence of hypertension in rural population. 2. To identify Bio-Social factors associated with hypertension. Study Design: A clinic based study was conducted in Rural Health Training Centre, Block Kirtinagar, District Garhwal of Uttarakhand which is also the field practice area of Department of Community Medicine, V.C.S.G. Govt. Medical Science & Research Institute. Material & Methods: All the patient attending the OPD were interviewed using pretested structured standard questionnaire. Two independent blood pressure reading were taken in sitting position. Hypertension was defined as Systolic blood pressure more than or equal to 140 mm Hg or Diastolic blood pressure more than or equal to 90 mm Hg or those individual currently taking antihypertensive treatment. Study Subjects: A total 1250 rural inhabitant; 19 year and above were screened. Out of which 562 were male & 688 were female. Study Period: January to July 2011. Study Variable: Age, Sex, Socio-economic status, Smoking, Alcoholism, BMI, Salt-Intake, Type of Family, Marital status, Literacy, Diabetes Mellitus, Family History, Occupation., Statistical Analysis: Chi-Square test, Standard error of difference between two mean. Result & Conclusion: Prevalence of Hypertension in rural population was 21.2%. Prevalence of Hypertension in male was 23.1% & in female it was 19.2%. Age, BMI, Salt-Intake, Smoking, Alcoholism, Diabetes Mellitus, Parental history were found to be significantly associated with hypertension.